2018
DOI: 10.1097/qai.0000000000001667
|View full text |Cite
|
Sign up to set email alerts
|

Time to First-Line ART Failure and Time to Second-Line ART Switch in the IeDEA Pediatric Cohort

Abstract: High rates of first-line failure and attrition were identified in children within 5 years after ART initiation. Of children meeting failure criteria, only one-third were transitioned to second-line ART within 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 18 publications
1
19
5
Order By: Relevance
“… Context: Differentiated care strategies are essential for meeting the needs of underserved groups and key populations who do not access routine services and/or require additional support to achieve optimal HIV outcomes . It is estimated that about 15% of patients on first‐line ART do not achieve viral suppression within 12 months , with children and adolescents more likely to have elevated viral loads . Moreover, even when patients fail to achieve viral suppression on first‐line ART, rates of regimen switching are lower than expected, and loss to care rates are high .…”
Section: Resultsmentioning
confidence: 99%
“… Context: Differentiated care strategies are essential for meeting the needs of underserved groups and key populations who do not access routine services and/or require additional support to achieve optimal HIV outcomes . It is estimated that about 15% of patients on first‐line ART do not achieve viral suppression within 12 months , with children and adolescents more likely to have elevated viral loads . Moreover, even when patients fail to achieve viral suppression on first‐line ART, rates of regimen switching are lower than expected, and loss to care rates are high .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies examined outcomes in people living with HIV-1 or HIV-2 who initiate ART, including determinants of mortality, of switching to second-line and third-line ART, drug resistance, loss to follow-up and the immunological and virological response to different ART regimens [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. For example, the African IeDEA regions contributed importantly to a large-scale analysis of outcomes in adolescents living with perinatally acquired HIV, which showed that HIV-associated mortality during adolescence was substantially higher in sub-Saharan Africa, South and Southeast Asia, and South America and the Caribbean than in Europe [36].…”
Section: Treatment Outcomes In Adults Adolescents Children and Pregmentioning
confidence: 99%
“…Smaller subnational cohorts can be unique in their ability to characterize experiences of patients and providers who may be in rural areas or district-level health care settings. 27 , 28 There are multiple regional and global research-focused pediatric cohort collaborations, including the European Pregnancy and Pediatric HIV Cohort Collaboration, 29 , 30 which links national cohorts across Europe with sites in Thailand, and the International Epidemiology Databases to Evaluate AIDS, 31 33 which brings together 6 regional pediatric cohort collaborations on 3 continents. Both use a common data exchange standard ( http://iedea.github.io/; http://www.hicdep.org/ ) to promote harmonization and facilitate comparison.…”
Section: National Databases and Cohorts Of Pediatric And Adolescent Dmentioning
confidence: 99%